STILL LIFE WORK OF FRUITS OF DIFFERENT COLORS ON A WHITE BACKGROUND - Jabbarov Botirsher Gulomovich (Web of Journals Publishing, 2024)
This article talks about the specific aspects of creating a realistic image of a still life consisting of various fruits on an elegant background with the help of watercolor paint, which is the main imaging tool of the science of painting in the field of education 60111200 - Fine arts and engineering graphics of higher educational institutions.
Keywords: This article talks about the specific aspects of creating a realistic image of a still life consisting of various fruits on an elegant background with the help of watercolor paint, which is the main imaging tool of the science of painting in the field of education 60111200 - Fine arts and engineering graphics of higher educational institutions.